Basal Cell Carcinoma Type Based on Histopathological Examination: Aggressive vs. Non-Aggressive - Fanny Fauziyyah Heryadi; Nugrohoaji Dharmawan; Prasetyadi Mawardi; Endra Yustin Ellistasari (Postgraduate, University of Mataram, 2025)
Histopathological subtypes of basal cell carcinoma (BCC) help determine prognosis and guide management. This study aimed to describe and compare the clinical and histopathological characteristics of aggressive and nonaggressive BCC. An observational descriptive study was conducted on 26 patients with biopsy-proven BCC. Hematoxylin and eosin (H&E) –stained sections were reviewed by an experienced pathologist. The nonaggressive group included nodular and superficial BCC, while the aggressive group included infiltrative and morpheaform BCC. Clinical and demographic data were recorded, and representative images were selected. Of the 26 cases, 13 were classified as aggressive and 13 as nonaggressive BCC. Female predominance was observed in both groups (61.54% vs. 69.24%). The mean age was 62.08 years in the aggressive group and 69.23 years in the nonaggressive group. Lesions were most frequently located in the nasal and zygomatic regions. The nodular subtype predominated among nonaggressive BCC (76.92%), while infiltrative (53.85%) and morpheaform (46.15%) subtypes were most common in the aggressive group. Histologically, nonaggressive subtypes exhibited well-circumscribed basaloid nests with palisading, whereas aggressive subtypes showed irregular cords within desmoplastic stroma and ill-defined margins. Histopathological examination remains the gold standard for differentiating aggressive from nonaggressive BCC, providing essential guidance for surgical planning and recurrence prevention.